2018
DOI: 10.1186/s40425-018-0337-7
|View full text |Cite
|
Sign up to set email alerts
|

Talimogene Laherparepvec combined with anti-PD-1 based immunotherapy for unresectable stage III-IV melanoma: a case series

Abstract: BackgroundTalimogene Laherparepvec (T-VEC) is an oncolytic virus approved as an intratumoral therapy for treating unresectable stage IIIB-IV metastatic melanoma. The mechanisms of action for T-VEC and checkpoint inhibitor are highly complementary. Recent studies have shown that combining checkpoint inhibitor therapy with T-VEC injection can lead to improved response rates for stage IIIB-IV melanoma patients.MethodsWe reviewed 10 consecutive cases of stage IIIC to stage IVM1b melanoma patients that received T-V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 18 publications
1
69
1
1
Order By: Relevance
“…The rationale for combining DC-ATA with checkpoint inhibitors also applies to this cytolytic virus product, namely the potential immune recognition of additional ATA. Encouraging results have been reported for combining this agent with anti-CTLA-4 and anti-PD-1 agents [46,47]. Combining DCV with intralesional cytolytic virus injection may be additive or synergistic because of the direct anti-tumor effects of the cytolytic virus.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for combining DC-ATA with checkpoint inhibitors also applies to this cytolytic virus product, namely the potential immune recognition of additional ATA. Encouraging results have been reported for combining this agent with anti-CTLA-4 and anti-PD-1 agents [46,47]. Combining DCV with intralesional cytolytic virus injection may be additive or synergistic because of the direct anti-tumor effects of the cytolytic virus.…”
Section: Discussionmentioning
confidence: 99%
“…with anti-PD-1 antibody for unresectable stage III-IV melanoma treatment, leading to an overall response rate (on-target lesions) of 90% (9/10) [201].…”
Section: Ipilimumabmentioning
confidence: 99%
“…We also contribute a case of cutaneous metastatic melanoma treated concurrently with TVEC and pembrolizumab, an anti‐PD1 immunotherapy, resulting in similar post‐injection robust lymphocytic infiltrate. A case series by Sun et al suggests that the combination of TVEC injections with checkpoint inhibitors such as pembrolizumab may provide a synergistic benefit. Of interest, Parekh et al also reported a case of TVEC administration inducing a neutrophilic (Sweet‐like) infiltrate.…”
Section: Patient and Biopsy Characteristics Of Tvecmentioning
confidence: 99%